Pengembangan Instrumen Tes Diagnostik Tiga Tingkat untuk Mengidentifikasi Miskonsepsi Peserta Didik pada Materi Pokok Laju Reaksi - Arifah, Maghfira; Jusniar, Jusniar; Anwar, Muhammad (Chemistry Education Review (CER), 2022)
This development research aims to produce a valid, consistent, and practical three-tier diagnostic test instrument to identify students' misconceptions on the subject matter of reaction rate. The instrument development referred to the Treagust model (1988) which was adapted by Jusniar et. al (2020) which consisted of the misconception proposition analysis stage, the test prototype development stage, and the test instrument quality test stage. The misconception proposition analysis stage was conducted by reviewing the literature to analyze the main concepts and misconceptions in reaction rate subject, while the prototype test development stage was conducted by compiling a three-tier diagnostic test instrument which was adapted to the misconception proposition analysis and the 2013 Curriculum. The test instrument quality test stage was conducted to examine the feasibility of instrument. The instrument used for the validity test was the instrument validation sheet given to two validators for the content validity test, followed by an inter-rater test. The empirical validity test instrument and the consistency test were three-tier diagnostic tests that were tested on students of grade XII MIA 1 in a limited trial. The practicality test employed teachers’ response questionnaires and students’ response questionnaires. The teacher’s response questionnaire were given to two chemistry teachers, while the students’ response questionnaires were given to 30 students of grade XII MIA 1 in a limited trial and again given to 111 students of grade XI MIA in a field trial. The results of the content validity test obtains an average value of 3.29 which is in valid category with an R value of 95% in the inter-rater test and the results of the empirical validity test obtain an average value of 0.45 at tier 1 and 0.43 at tier 2 with valid category. The results of the consistency or reliability test obtains Cronbach's Alpha coefficient of 0.87 at tier 1 and 0.86 at tier 2, which is in high reliability category. The results of the practicality test using the teachers’ response questionnaire obtains 95.83%, the students’ response questionnaire in limited trial is 89.17%, and the students’ response questionnaire in field trial is 88.63%. The results obtained in the three practicality tests are in very practical category. The results of testing the three-tier diagnostic test instrument on the reaction rate subject obtain 69.55% of students in understanding category, 27.50% of students is in in less understanding category, and 2.95% of students is in misconception category.